PERAN OBJEK WISATA AGUSEN DALAM MENAMBAH PENDAPATAN MASYARAKAT (STUDI DI GAMPONG AGUSEN KECAMATAN BLANGKEJEREN KABUPATEN GAYO LUES) - Sakdiah, Sakdiah; Zulfadli, Zulfadli; Sulaimasyah, Sulaimasyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The Role of Agusen Tourism Objects in Increasing Community Income (Study in Agusen Village, Blangkejeren District, Gayo Lues Regency). Tourism is an activity that directly touches and engages the community, thus bringing various impacts on the local community. As for the problems in this paper are (1) How the role of the agusen tourist attraction in increasing the income of the people who are in the Agusen Village, Blangkejeren District, Gayo Lues Regency. (2) What factors support and hinder Agusen tourism objects in increasing the people's income in Agusen Village, Blangkejeren District, Gayo Lues Regency. This study aims to determine the role of Agusen attractions in increasing community income in the Agusen Village, Blangkejeren Subdistrict, Gayo lues Regency, and also to find out the supporting factors and inhibiting the role of attractions in increasing the income of Agusen Gampong Subdistricts, Blangkejeren District, Gayo Lues Regency. To obtain the data the author uses a qualitative method, with a descriptive analysis approach, while the data collection techniques used are observation, interviews and documentation. From the results of the study it can be that: the existence of attractions in increasing community income is a shared responsibility. The existence of attractions can be said to be quite successful in increasing the income of the community in the Agusen Village, Blangkejeren District, Gayo Lues Regency. The supporting factors for Agusen attractions are the good cooperation between the community, the government and the village apparatus. As for the inhibiting factor is due to the absence of specific regulations either from the village or the government so that there are still irregularities in carrying out the task of adding to the community's income in the Agusen Village, Blangkejeren District, Gayo Lues Regency.Keywords: Role, Tourism Objects, Community Income.